Laboratories for Global Space-Time: Science-Fictionality and the World's Fairs, 1851-1939. - Luckhurst, Roger (Science Fiction Studies, 2012)
This article examines the world's fair movement between The Great Exhibition of 1851 and The New York World's Fair of 1939, suggesting that these sites are science-fictional spaces that expose their mass audiences to forms of space-time compression that enable early figurations of globalization. Fair sites embody specific forms of economic transfer and exchange that anticipate dreams of the borderless flows of capital in some current versions of globalization theory. This "sfnal" condition of the world's-fair site is not just in the futuristic displays of techno-scientific "progress," which became an insistent form of spectacle in the world's fair, but also in the spatialization of developmental histories, reading conceptions of modernity remorselessly through hierarchies of racial "progress" or spectacles of anachronistic "arrest" or degenerative "decline." Long before the famous Futurama of 1939 New York, world's fairs were one of the first spaces in which large populations experienced deliberate and sustained disadjustment in time within a bounded zone, an early sense of immersion in the "science-fictional."